Perbedaan Aktivitas Antioksidan pada Minuman Tradisional Wedang Uwuh Original, Seduh, Celup, Instan dan Sirup - Retnosyari Septiyani; Elok Rahmawati (CHEMICA: Jurnal Teknik Kimia, 2019)
Wedang uwuh as a distinctive traditional beverage from Imogiri Yogyakarta has been widely known to the wider community and even began to develop a lot like wedang uwuh in the form of the original herb, brewed, dipped, instant and syrup. However, research on wedang uwuh is still very limited. Therefore this study aims to conduct a proximate analysis test on the original wedang uwuh, brewed, dipped, instant and syrup so that the chemical content is known and to test antioxidant activity so that it can provide information to the public about the types of variants of wedang uwuh which has the best antioxidant activity. Antioxidants are important for our health. The importance of antioxidants for maintaining the physiological functions of the vital organ in our body. Based on the results of proximate testing, wedang uwuh brewed and dipped have lower energy compared to wedang uwuh original, instant, and syrup. Testing of antioxidant activity using DPPH and IC50 methods showed that the brewed water had the highest antioxidant activity value compared to the original, dip, instant and syrup variants with an IC50 value of 9195.40 ppm. Factors that influence the difference in antioxidant activity in the original, brewed, instant and syrup include mechanical treatment, heat treatment, exposure to light, and packaging used during storage.